STAD Learning Model Using the Problem Solving Method for Critical Thinking in Grade IV Elementary School Students - Isma, Isma indiyah farikhah; Fanny, Arif Mahya (Jurnal Pendidikan Sekolah Dasar, 2024)
The purpose of this study was to determine the effect of the Student Teams Achievement Division learning model with the Problem Solving method on critical thinking of 4th grade students at SDN Dukuh Menanggal 1 Surabaya.The research design in this study is experimental quantitative research. The research design used is nonequivalent control group design with posttest-only control design type. The sample and population were all fourth grade students of SDN Dukuh Menaggal consisting of two classes with a total of 62 students, namely class IV A of 31 students and class IV B of 31 students. The sampling technique in this study used saturated sampling. The research instrument used was a test. It was obtained that the average value (mean) of the posttest in the experimental class was 79.03, while for the average value (mean) in the control class was 69.03. From the calculation using t-test analysis and the results of the analysis obtained a Sig value. (2 tailed) 0.000. Then obtained Sig. (2 tailed) α 0.05 or 0.000 <0.05. Then H0 is rejected and H1 is accepted. That students who are taught using the STAD learning model with the Problem Solving method on students' critical thinking show higher results. So it can be said that learning IPAS material on Indonesian cultural wealth using the STAD learning model with the Problem Solving method on critical thinking of fourth grade students of SDN Dukuh Menanggal 1 Surabaya is more effective than conventional learning.